2006
DOI: 10.1111/j.1745-7254.2006.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blocking activity of calycosin, a major active component of Astragali Radix, on rat aorta1

Abstract: Aim: To investigate the vasoactivity of calycosin, a major active component of Astragali Radix. Methods: Experiments were performed on isolated rat thoracic aortic rings pre-contracted with phenylephrine (PHE) or KCl. Results: Calycosin produced a concentration-dependent relaxation on the tissue pre-contracted using PHE with 4.46±0.13 of pD 2 and 95.85%±2.67% of E max ; or using KCl with 4.27±0.05 of pD 2 and 99.06%±2.15% of E max , and displaced downwards the concentration-response curves of aortic rings to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…Besides, we also observed some discrepancies in the effects of calycosin and formononetin in blood vessels from various vascular beds. Previous study intact aortic rings reported that the relaxation elicited by calycosin was endothelium-independent by acting as Ca 2+ channel blocker [7]. However, here in rat mesenteric arteries we observed that calycosin-elicited relaxation is both endothelium-dependent and endothelium-independent.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Besides, we also observed some discrepancies in the effects of calycosin and formononetin in blood vessels from various vascular beds. Previous study intact aortic rings reported that the relaxation elicited by calycosin was endothelium-independent by acting as Ca 2+ channel blocker [7]. However, here in rat mesenteric arteries we observed that calycosin-elicited relaxation is both endothelium-dependent and endothelium-independent.…”
Section: Discussioncontrasting
confidence: 58%
“…Previous studies have shown that calycosin and formononetin produced antihypertensive effects and improved endothelial and cardiovascular functions [36]. They have been shown to display vasoactive effects in various vascular beds [3, 57]. In rat aorta, calycosin induced vasodilation mainly by inhibiting voltage-dependent Ca 2+ channel (VDCC) in vascular smooth muscle [7], while formononetin caused vasodilation by releasing nitric oxide (NO) in endothelial cells, as well as by the activation of large-conductance Ca 2+ -activated K + (BK Ca ) and ATP-sensitive potassium (K ATP ) channels in aortic smooth muscle cells [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that inhibition of calcium influx might be involved in the observed vasorelaxant effect. Inhibition of vascular calcium current has also been reported for the natural flavonoid calycosin isolated from Astragali radix, the flavonoid containing extract of Sarcococa saligna, and the plant-flavonoid catechin [17][18][19]. Effects of the main green tea flavonoid epigallocatechin (EGCG) on vascular preparations have been studied in detail.…”
Section: Effects Of Flavonoids On Vascular Calcium Currentmentioning
confidence: 99%
“…In the present study, the CM approach was adopted for the assessment of the efficacy of a Chinese herbal formula, Slimpid, in patients possibly with MS or at risk of developing MS. Though the actual mechanism of the treatment efficacy is not yet known, most of the ingredients of Slimpid are traditionally believed to exert anti-ageing effects [23], possibly by regulating both Yin and Yang, via regulating endocrine and metabolic functions. Such effects refer to as "supplementing Qi to strengthen Pi" and "eliminating inner-heat and dampness" in the context of Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%